The utilization of reclaimed water: Possible risks arising from waterborne contaminants. (November 2019) - Deng, Shenxi; Yan, Xueting; Zhu, Qingqing; Liao, Chunyang
Abstract: Increasing interest of seeking substitutable water resources accrues from shortage of freshwater. One of the options considered is reclaimed water (also designated as recycled water) that has been widely used in daily life. Although reclaimed water can serve as a feasible reliever of water pressure, attention about its technologies and potential risks is growing in the meantime. Most established wastewater treatment plants (WWTPs) predate many new contaminants, which means treatment processes cannot ensure to dislodge certain contaminants completely from origin water. Furthermore, a wide range of factors, such as seasons and influent variations, affect occurrence and concentration of reclaimed water-borne contaminants, making research about quality of reclaimed water especially significant. Many reclaimed water-borne contaminants, including biological and chemical contaminants, are toxic to human health, and complex wastewater matrix may aggravate water quality of concern. The widespread use of reclaimed water continues to be a concern on agriculture, ecological environment and human health. This study aims to: 1) provide a critical review about occurrence and profiles of diverse contaminants in the treated reclaimed water, 2) discuss the possibility to avoid the secondary pollution in reuse of reclaimed water, and 3) reveal the prospective consequences of using reclaimed water on agriculture, ecological environment and human health. Graphical abstract: Image 1 Highlights: Conventional WWTPs produce reclaimed water that contains various contaminants. The potential risks of reclaimed water to the environment and humans were reviewed. Regulations and strategies for use of reclaimed water are urgent to make. Further studies are needed to elucidate the fate and risk of waterborne contaminants. Abstract : Possible risks arising from wastewater-borne contaminants were reviewed and future line of research on the utilization of reclaimed water is recommended.